# Example 4

Last updated at May 29, 2018 by Teachoo

Last updated at May 29, 2018 by Teachoo

Transcript

Example 4 Find the anti derivative F of f defined by = 4 3 6, Where F (0) = 3 =4 3 6 Some F is Anti derivative F = = 4 3 6 = 4 3 6 = 4 3 6 =4 3 6 1. =4 3 6 0 =4 3 6 0 = 4 . 3 + 1 3 + 1 + 1 6 0 + 1 0 + 1 2 = 4 . 4 4 + 1 6 1 1 2 = 4 + 1 6 2 = 4 6 + 1 2 = 4 6 + So, F = 4 +6 + Given F 0 =3 So, F = 4 +6 + 3=0+0+ C = 3 So, F = + +

Example 1

Example 2

Example 3

Example 4 You are here

Example 5

Example 6

Example 7

Example 8

Example 9 Important

Example 10 Important

Example 11

Example 12

Example 13

Example 14

Example 15 Important

Example 16

Example 17

Example 18

Example 19

Example 20 Important

Example 21

Example 22 Important

Example 23

Example 24

Example 25 Important

Example 26

Example 27 Important

Example 28

Example 29

Example 30 Important

Example 31

Example 32

Example 33

Example 34 Important

Example 35

Example 36 Important

Example 37

Example 38

Example 39

Example 40 Important

Example 41 Important

Example 42

Example 43 Important

Example 44 Important

Example 25 (Supplementary NCERT)

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 8 years. He provides courses for Maths and Science at Teachoo. You can check his NCERT Solutions from Class 6 to 12.